The therapist's answer book : solutions to 101 tricky problems in psychotherapy - Blackman, Jerome S. (Routledge, 2013)
"Therapists inevitably feel more gratified in their work when their cases have better treatment outcomes. This book is designed to help them achieve that by providing practical solutions to problems that arise in psychotherapy, such as: Do depressed people need an antidepressant, or psychotherapy alone? How do you handle people who want to be your friend, who touch you, who won't leave your office, or who break boundaries? How do you prevent people from quitting treatment prematurely? Suppose you don't like the person who consults you? What if people you treat with CBT don't do their homework? When do you explain defense mechanisms, and when do you use supportive approaches? Award-winning professor, Jerome Blackman, answers these and many other tricky problems for psychotherapists. Dr. Blackman punctuates his lively text with tips and snippets of various theories that apply to psychotherapy. He shares his advice and illustrates his successes and failures in diagnosis, treatment, and supervision. He highlights fundamental, fascinating, and perplexing problems he has encountered over decades of practicing and supervising therapy. "--